2019
DOI: 10.1088/1755-1315/336/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Loss and gain of the bird species after the establishment of oil palm plantation in South Sumatra

Abstract: The development of oil palm has been documented as one of factor caused deforestation leading to the loss of biodiversity, however, to what extent the impacts of oil palm conversion on biodiversity in South Sumatra remain little-known. To answer this issue, we studied the diversity of bird in the area before and after oil palm established by calculating species number, richness, evenness, similarity, and composition. Secondary forest, shrubs and rubber plantation were identified as area before oil palm establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The study result showed that YOP land cover had the highest H' Index, Dmg Index, the total number of individuals, and the total number of species. Other studies in Kalimantan and Sumatera also showed that young growth oil palm has the highest species diversity compared to medium and old-growth oil palm (Erniwati and Santosa 2019;Yudea and Santosa 2019). Furthermore, harvesting activities in medium and old-growth oil palm land cover caused undergrowth to be less dense than the young growth oil palm plantation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The study result showed that YOP land cover had the highest H' Index, Dmg Index, the total number of individuals, and the total number of species. Other studies in Kalimantan and Sumatera also showed that young growth oil palm has the highest species diversity compared to medium and old-growth oil palm (Erniwati and Santosa 2019;Yudea and Santosa 2019). Furthermore, harvesting activities in medium and old-growth oil palm land cover caused undergrowth to be less dense than the young growth oil palm plantation.…”
Section: Discussionmentioning
confidence: 95%
“…Yudea and Santosa (2019) said that conversion from secondary forest and shrubs into oil palm plantations increased bird number of species and bird species composition. At the same time, the conversion also had an impact on species lost that caused by those species cannot fit in oil palm plantation habitat (Azhar et al 2013;Srinivas and Koh 2016;Erniwati and Santosa 2019;Yudea and Santosa 2019). Existing oil palm plantations can be made more hospitable to wildlife through various modifications, even the most wildlife-friendly oil palm plantations are a poor habitat compare to forests (Koh 2008;Gilroy et al 2014;Srinivas and Koh 2016;Kissinger et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, to estimate the amount of mammal species loss and gain, analysis was used is making a list of the types of mammals found in each land cover and counting the species number in the land cover before and after oil palm plantation (Nugroho and Santosa, 2018;Erniwati and Santosa, 2019). The species found in this study are also categorized based on feeding guild.…”
Section: Discussionmentioning
confidence: 99%
“…Meijide et al (2018) stated that the conversion of tropical forests to oil palm plantations also affects the microclimate condition and the loss of biodiversity. The conversion of secondary forests to oil palm plantations impacted on loss and gain of several communities such as bird, mammal, herpetofauna, butterfly, and soil macroinvertebrate (Erniwati and Santosa, 2019;Ginoga et al, 2019;Santosa and Rejeki, 2019;Yeo et al, 2020). Similar to secondary forests, the land cover change from shrubs to oil palm plantation can affect species diversity of tropical vegetation and wildlife species such as herpetofauna and mammal (Nugroho and Santosa, 2018;Hilwan and Santosa, 2019;Rahmadiyanti and Santosa, 2019;Al-Faritsi and Santosa, 2021).…”
Section: Introductionmentioning
confidence: 99%